Crossed interactions (pathogens, symbionts, vectors) in pathosystems : Example of the soft tick Ornithodoros and the African swine fever virus. - (:unkn) unknown (My University, 2024)
Vector-borne diseases account for 17% of the global burden of infectious diseases affecting human populations. A vector-borne disease results from complex interactions between the transmitted pathogen, the vertebrate host, the vector, its microbiota, and the environment. These different actors influence the incidence of the disease, its geographical distribution, and its epidemiology. Among arthropod vectors, ticks are capable of transmitting the widest variety of pathogens (viruses, bacteria and parasites).From a veterinary health point of view, Afrotropical soft ticks of the genus Ornithodoros are vectors of the African swine fever (ASF) virus, a hemorrhagic fever often fatal in its acute forms in domestic pigs. In southern Africa, ticks play an important role in the sylvatic cycle of ASF by transmitting the virus to wild suids (bushpigs and warthogs). The latter show no clinical signs of the disease, but develop a viremia. Little is known about how the virus is transmitted to domestic pigs, or about the involvement of ticks in the domestic cycle. These issues are the subject of the international NifNaf project, funded by the USDA and NSF (https://www.asf-nifnaf.org/ 2020-2023), in which this PhD takes part.In this context, this PhD work focuses on the interactions between Ornithodoros ticks - the virus of interest (ASF) - the tick microbiota and their influence on the epidemiology of the disease. My objective was to characterize, in southern Africa, the spatial dynamics of ticks of the Ornithodoros moubata complex, in relation with the circulation of the ASF virus and interactions with the microbiota. This required (i) to define the spatial dynamics and genetic diversity of ticks in the wild and to assess the possibility of migration to the domestic environment, (ii) to assess the biological functions and origin of the microbiota in ticks, and finally (iii) to study potential interactions between the ASF virus and the tick microbiota.To this end, fi
Keywords: African Research